A RARE CASE OF FUNCTIONAL METASTATIC FOLLICULAR THYROID CARCINOMA WITH EGGSHELL CALCIFICATION - NG, Yong Siang; Tong, Chin Voon (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Only a few cases of follicular thyroid carcinoma (FTC) with eggshell (or rim-like peripheral) calcification have been reported. Here, we report a rare case of functional metastatic FTC with eggshell calcification. CASE A 57-year-old female presented with progressive neck enlargement, dysphagia, and weight loss of 10 kg over 2 months. She also had a hoarse voice. On examination, she appeared thyrotoxic. She had a palpable 3 x 4 cm mass over the left neck, which was hard in consistency and immobile. Biochemically, she was hyperthyroid with suppressed TSH and high free T4 of 67.9 pmol/L (7.9-14.4). Her chest radiograph showed an eggshell calcification over the neck region with right tracheal deviation. Her neck ultrasound showed a thyroid nodule (ACR TI-RADS 5). CT scan revealed a left thyroid nodule (3.3 x 3.2 x 3.7 cm) with peripheral coarse calcifications. Mass effects were seen on the adjacent vessels, trachea, and oesophagus. Left vocal palsy was likewise noted. There was a destructive lytic soft tissue lesion seen at the manubrium of the sternum with multiple suspicious lung nodules. FNAB of the thyroid and sternal lesions demonstrated Bethesda II follicular lesions. She underwent thyroid surgical resection with histopathologyconfirmed widely invasive FTC. Postoperatively, she remained thyrotoxic for which radioactive iodine therapy was given subsequently. CONCLUSION Functional thyroid carcinoma (TC) is rare with the FTC subtype being more prevalent (especially the metastatic disease) and having a less favourable prognosis. FNAB cannot distinguish FTC from benign follicular neoplasm, hence, histologic evaluation of the thyroid specimen is required. About 40-60% of patients with eggshell calcification within the thyroid gland were reported to be malignant and commonly in papillary TC. Sonographic features of a peripheral halo with discontinuity of the calcification are predictive of malignancy. Thyroid carcinoma should be considered in patients with aggressive symptoms and presence of eggshell calcification on radiograph.